Myrmecridium hydei, a novel marine species from Thailand - Asghari, Raheleh; Phukhamsakda, Chayanard; Karimi, Omid; Apurillo, Carlo Chris S.; Jones, E.b. Gareth (Phytotaxa, 2023)
Myrmecridium hydei was isolated from decaying branch of Areca species submerged in seawater from Prachuap Khiri Khan Province, Thailand. The new species is supported by phylogenetic analysis of combined ITS and LSU sequence data. Myrmecridium hydei formed a distinct clade from M. phragmitigenum, M. phragmiticola and M. sambuci with moderate statistical support. The species also differs from other Myrmecridium species by having a longer sympodial, straight or flexuous to geniculate-sinuous conidiophore and obovoid or fusoid to irregular, guttulate conidia without a wing-like sheath. Myrmecridium hydei is described as a novel species based on morphology and phylogeny.